2D seismic interpretation and characterization of the Hauterivian–Early Barremian source rock in Al Baraka oil field, Komombo Basin, Upper Egypt. (March 2018) - Ali, Moamen; Darwish, M.; Essa, Mahmoud A.; Abdelhady, A.
Abstract: Komombo Basin is located in Upper Egypt about 570 km southeast of Cairo; it is an asymmetrical half graben and the first oil producing basin in Upper Egypt. The Six Hills Formation is of Early Cretaceous age and subdivided into seven members from base to top (A–G); meanwhile the B member is of Hauterivian–Early Barremian and it is the only source rock of Komombo Basin. Therefore, a detailed study of the SR should be carried out, which includes the determination of the main structural elements, thickness, facies distribution and characterization of the B member SR which has not been conducted previously in the study area. Twenty 2D seismic lines were interpreted with three vertical seismic profiles (VSP) to construct the depth structure-tectonic map on the top of the B member and to highlight the major structural elements. The interpretation of depth structure contour map shows two main fault trends directed towards the NW-SE and NE to ENE directions. The NW-SE trend is the dominant one, creating a major half-graben system. Also the depth values range from −8400 ft at the depocenter in the eastern part to −4800 ft at the shoulder of the basin in the northwestern part of the study area. Meanwhile the Isopach contour map of the B member shows a variable thickness ranging between 300 ft to 750 ft. The facies model shows that the B member SR is composed mainly of shale with some sandstone streaks. The B member rock samples were collected from Al Baraka-1 and Al Baraka SE-1 in the eastern part of Komombo Basin. The results indicate that the organic matter content (TOC) has mainly good to very good (1–3.36 wt %), The B member samples have HI values in the range 157–365 (mg HC/g TOC) and dominated by Type II/III kerogen, and is thus considered to be oil-gas prone based on Rock-Eval pyrolysis, Tmax values between 442° and 456° C therefore interpreted to be mature for hydrocarbon generation. Based on the measured vitrinite equivalent reﬂectance values, the B member SR samples have a range 0.7–1.14%Ro, in the oil generation window. Highlights: The B member (Hauterivian-Early Barremian) is the only source rock of Komombo Basin. The interpretation of depth structure contour map shows two main fault trends directed towards the NW-SE and NE to ENE directions. The NW-SE trend is the dominant one, creating a major half-graben system. The Isopach contour map of the B member shows a variable thickness ranging between 300 ft in the northwestern part to 750 ft in the eastern part of the study area. The results of the B member samples indicate that the organic matter content (TOC) has mainly good to very good (1–3.36 wt %), HI values range from 157 to 365 (mg HC/g TOC) and dominated by Type II/III kerogen. Tmax values of the B member SR between 442° and 456° C therefore interpreted to be mature for hydrocarbon generation.The B member SR samples have a range 0.7–1.14%Ro, in the oil generation window.